Ontological commitment model for quality improvement research in community health domain - Wannapa Pipattanawong (2018)
© 2015, Kasetsart University. All Rights Reserved. Community-based nursing colleges in developing countries face difficulties in achieving research quality performance due to heavy teaching workloads and a commitment to support students in practice placements. This research aimed to develop the Ontological Commitment Model for research initiative and to assert the effectiveness of this model for quality improvement in a nursing college in Chiang Mai, Thailand. Quality Improvement Research was applied and used card sorting and ontological analysis tools on the conceptual framework in order to practically transform routine work into research opportunities under a compulsory educational quality model. To gain research initiatives, keywords were extracted that related to the Baldridge Quality Model which encompasses organizational profile, leadership, strategic planning, customer focus, measurement, analysis, knowledge management, workforce focus, operation focus, and results. The research direction of the nursing college was used to extract keywords from the current Thai National Government guidelines, and the specialty or interests of knowledge workers from six participants who had no experience in research and the head of a research team who had more than three years experience were recruited in this study. The results revealed that the Ontological Commitment Model using card sorting can help participants more rapidly achieve research initiatives than their prior experiences. The findings showed quality improvement in the research received from ontological commitment significantly helped staff to reduce their working time in routine work and to undertake research efficiently, to increase success in designing conceivable plans that integrated teaching and conducting research, and to raise their Baldridge quality scores. In particular, the benefits included an increment in the number and quality of submitted research projects and improved faculty research capacity. Increased research productivity will support the college’s academic operation as a center of excellence in addiction studies.